Derivational and Semantic Relations of Croatian Verbs - Šojat, Krešimir (Array, 2012)
The paper deals with morphosemantic relations between Croatian verbs and discusses their inclusion in Croatian WordNet. The morphosemantic relations refer to semantic relations between unprefixed infinitives and their prefixed derivatives. We introduce the criteria for the division of aspectual pairs and further discuss verb prefixation which results in combinations of prefixes and base forms that can vary in terms of meaning from compositional to completely idiosyncratic. The focus is on the regularities in semantic modifications of base forms modified by one prefix. The aim of this procedure is to establish a set of morphosemantic relations based on regular or reoccuring meaning alternations.